Manganês na nutrição e na produção de massa seca do capim-mombaça - Checchio Mingotte, Fabio Luiz [UNESP]; Rodrigues dos Santos, Carlos Leandro; Prado, Renato de Mello [UNESP]; Flores, Rilner Alves; Togoro, Aluisio Hideki; dos Santos da Silva, Juliana Aparecida; Politi, Lucas Sanches; Pinto, Anderson Santos; Aquino, Daily Soraya (Universidade Federal de Uberlândia (UFU), 2011)
There are few studies that relate the micronutrient manganese nutritional status and production of fodder. The objective was to evaluate the application of manganese in the nutrition and growth of Mombaca grass. The completely randomized design was used with five manganese levels (0, 15, 30, 60, 120 mg dm(-3)) and four replicates. Each experimental unit consisted of a pot filled with 3.5 dm(-3) of soil from Oxisol (Mn = 0.6 mg dm(-3)), containing four plants. Two harvests were set, the first 44 days after sowing and the second 38 days after the first cut. The concentration of manganese in the soils, the manganese content of leaves, number of tillers, plant height, shoot dry mass in each slice and the root system of Mombaca grass were evaluated. The applied rates of manganese resulted in increased accumulation of Mn in the plant, and there was an increase in dry mass of Mombaca grass, with maximum production, obtained from derivation, of 5.9 and 6.3 g plant(-1) for levels of 121 and 71 mg dm(-3) of Mn in the first and second cut respectively. The Mombaca grass has showed high manganese's tolerance, the critical level of toxicity was 841 mg kg(-1) in the second cut.

São poucos os estudos que relacionam o micronutriente manganês com o estado nutricional e a produção de forrageiras. Objetivou-se avaliar o efeito da aplicação de manganês na nutrição e no crescimento do capim Mombaça durante dois ciclos de produção. O delineamento experimental foi inteiramente casualizado, constituídos de cinco doses de manganês (0, 15, 30, 60, 120 mg dm-3) e quatro repetições. Cada unidade experimental foi constituída de um vaso preenchido com 3,5 dm3 de terra proveniente de um Latossolo Vermelho distrófico (Mn = 0,6 mg dm-3), contendo quatro plantas. Realizou-se dois cortes, o primeiro aos 44 dias após a semeadura e o segundo 38 dias após o primeiro corte. Avaliaram-se a concentração de manganês no solo, o teor de manganês foliar, o número de perfilhos, altura de plantas, massa seca da parte aérea em cada corte e do sistema radicular. As doses de manganês aplicadas proporcionaram aumento no acúmulo de Mn na planta, bem como houve incremento na produção de massa seca do capim Mombaça, com produção máxima de 5,9 e 6,3 g planta-1, para as doses de 121 e 71 mg dm-3 de Mn, nos primeiro e segundo cortes respectivamente. O capim Mombaça apresentou alta tolerância ao manganês, tendo como nível crítico de toxicidade 841 mg kg-1, ocorrido apenas no segundo corte da forrageira.
Manganese in the nutrition and dry mass production of the mombaça grass
Keywords: Panicum maximum; Soil fertility; Micronutrient; Toxicity; Pasture